We care nursery: nursery care services / Muhamad Taufiq Hidayat Ahmad [et al.] - Ahmad, Muhamad Taufiq Hidayat; Roszi, Nur Izzati; Omar, Nurfarahin; Jaafar, Nurshuhadah; Ramli, Siti Najirah; Mohd Sani, Siti Nor Fatin (2013)
Nowadays, we can see a lot of people get involve in business. This is due to the profit that can be made through business as what stated in Al-Quran "Business is 9/10 of sustenance sources. Service on nursery is really need by so many parents as they do not have so much time to look after their child.